Two new genera and six new species of Stenosini (Coleoptera: Tenebrionidae: Pimeliinae) from Myanmar (Burma), collected by René Fouquè - Schawaller, Wolfgang; Bigalk, Sonia (Zootaxa, 2021)
New taxa of the tenebrionid tribe Stenosini Schaum, 1859 (subfamily Pimeliinae Latreille, 1802) from central Myanmar (Burma) in the region around Mandalay are described: Bamarosis gen. nov. fouquei sp. nov. (subtribe Dichillina), Shanosis gen. nov. renei sp. nov. (subtribe Dichillina), Gebieniella ellenae sp. nov., Gebieniella matthiasi sp. nov., Stenosis helenae sp. nov., Stenosis mandalayca sp. nov. The proposed subgenera in some genera of Stenosini, based on certain species, but not on complete revisions of the corresponding genera remain doubtful and are not considered herein. A checklist of all taxa of Stenosini known from Burma is added.